Reverse logistics and product identification: theoretical review for electroelectronic industry - de Oliveira, Uanderson Rebula (2016)
The electrical and electronic products sales grow in close connection to technological innovations and the speed in which they become obsolete, reflecting in the increase of a discarded residue called Waste Electrical and Electronic Equipment (WEEE) or E-waste. From the disposal of electronics devices such as desktops, notebooks, printers and cell phones, e-waste is a major problem because it contains many substances harmful to the environment and to human health. Thus, it becomes necessary to a proper disposal. With the creation of the National Policy on Solid Waste (PNRS) in Brazil, manufacturers, importers, distributors and retailers of electrical and electronic products and their components must structure and implement reverse logistics systems (LR) upon return of the products after use by the consumer. Although many companies in the consumer electronics industry worry about the LR of its products, the literature review indicates few results, showing lack of work on the topic. The article analyzes the panorama of LR and its interrelation with e-waste and identification technology products, with the purpose of contributing to the practice of PNRS. To this end, a systematic review of literature, involving Reverse Logistics, E-waste and product identification technologies was held. By a case study, SmartWaste Project from Hewlett-Packard (HP), it can be inferred that the Barcode and Radio Frequency Identification (RFID) technologies are useful and viable to improve the RL practices applied to e-waste.